Peran Guru Dalam Meningkatkan Motivasi Pembelajaran Tematik - Mariana; Hamdani, Muh.; Belik Dwipa, Lalu (STAI AL-AMIN, 2025)
The purpose of this study was to explore and explore the role of fourth-grade teachers at SDN 1 Loloan in increasing motivation in thematic learning. This research was conducted in a motivator and facilitator role, ensuring students were sufficiently motivated to participate in teaching and learning activities. The teacher's role has been well-exemplified, as seen in providing motivation in various ways. They provide motivational stories and activities that can increase student enthusiasm and motivation. They provide good examples and role models for motivation for students. They communicate motivation that influences learning. They provide facilities in the form of media or learning methods and guidance to both motivated and unmotivated students. They provide praise, prizes, and grades that can increase student motivation and create individual and group competitions to stimulate enthusiasm and motivation. They also conduct assessments in terms of attitudes, behavior, and knowledge. Thus, the teacher's role is crucial in providing motivation in thematic learning activities. The impact of providing motivation is a sense of interest and enjoyment in students participating in learning activities.